Implementasi Manajemen Risiko dan Dampaknya terhadap Kinerja Keuangan pada Perusahaan PT API di Indonesia - Nur Amalia Ramadhan; Isti Rahayu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the implementation of risk management at PT API, identify the challenges faced during the process, and evaluate its impact on the company’s financial performance. A qualitative research approach was employed, with data collected through in-depth interviews, direct observation, and documentation review. The data were obtained from managers and staff of the Quality, Risk, and Performance Management unit, providing comprehensive insights into the risk management procedures applied within the company. The findings reveal that PT API has implemented risk management in accordance with the ISO 31000:2018 framework. The processes of risk identification, analysis, evaluation, and mitigation are carried out systematically. However, several challenges were identified that hinder effective implementation. These include reliance on manual monitoring systems, which are prone to errors and delays in reporting, and the lack of widespread awareness of risk culture across all work units. This uneven awareness results in suboptimal employee participation in risk identification and reporting. Nevertheless, the implementation of risk management has shown a positive impact on the company's financial performance. With structured risk treatment and appropriate mitigation strategies, the company has been able to reduce potential financial losses and improve operational efficiency. This is reflected in more controlled budget management and more cautious decision-making based on risk analysis. Overall, the study emphasizes that consistently and thoroughly applied risk management not only functions as a control mechanism but also contributes significantly to the financial stability and sustainability of the company. Therefore, the enhancement of digital monitoring systems and the strengthening of risk awareness across all departments are crucial aspects that need to be addressed moving forward.This research highlights the strategic value of risk management in supporting organizational resilience and financial health, offering practical insights for companies seeking to optimize their risk governance frameworks.